Pendampingan Pembuatan Laporan Keuangan Peternak Ikan Lele Di Desa Kunduran - Andreas, Rocky; Susanti, Neri (Jurnal Kewirausahaan & Inovasi, 2024)
In carrying out business activities, both individuals and business entities should make financial reports. Financial statements are the main or final result of an accounting process which is information material for owners and parties who need it, financial statements are an indicator of the success of a business activity that is carried out. Therefore, the importance of financial statements. Training and mentoring is needed not only for large businesses, but also small businesses such as catfish farmers in Kunduran Village, East Seluma District. The lack of knowledge in making financial statements and awareness of the importance of making financial statements in the farming community, especially catfish farmers, so that they do not know whether their business is feasible or not to be developed in the future. Therefore, a good understanding of the importance of making financial reports is needed to improve the results of the business they are engaged in.